2017
DOI: 10.3390/geosciences7010012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry and 222Rn Concentrations in Spring Waters in the Arid Zone El Granero, Chihuahua, Mexico

Abstract: Abstract:Water in arid and semi-arid environments is characterized by the presentation of complex interactions, where dissolved chemical species in high concentrations have negative effects on the water quality. Radon is present in areas with a high uranium and radium content, and it is the main contributor of the annual effective dose received by humans. The objective of this study was to evaluate concentrations of 222 Rn and the water quality of spring waters. Water was classified as calcium sulfated and sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…According to [6], high radon concentrations are caused by the convection process, which is more dominant in gas movements than diffusion. Another study concluded that radon emanation from four active fault zones in California was greater than the concentration of the background radon in the area [7]. This greater concentration is due to the higher outgassing rates in the anomaly zones caused by high permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [6], high radon concentrations are caused by the convection process, which is more dominant in gas movements than diffusion. Another study concluded that radon emanation from four active fault zones in California was greater than the concentration of the background radon in the area [7]. This greater concentration is due to the higher outgassing rates in the anomaly zones caused by high permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Radon concentrations in water have also been studied by [7] in a geothermal area; it was found that high dissolved 222 Rn concentrations are associated with high concentrations of sulfate, fluoride and total dissolved solids related to geothermal water. In contrast to [7], 222 Rn concentrations from thermal manifestation in some fields in New Zealand, such as Wairakei, Waiora, Spa and Rotokaua, show that water temperature does not correlate with 222 Rn concentrations in water [8].…”
Section: Introductionmentioning
confidence: 99%